The Role of Husbands in Supporting Breastfeeding Adequacy Among Postpartum Working Mothers Attending Darussalam Public Health Center - Safitri, Mey Elisa; Aziz, Aniza Abd.; Hassan, Nurulhuda Mat (Journal La Medihealtico, 2024)
The WHO recommends exclusive breastfeeding for the first 6 months; however, coverage remains low, particularly among working mothers who face various challenges. Husband involvement is a key factor in breastfeeding success. To analyze the role of husbands in improving breastfeeding practices among postpartum working mothers in the working area of Darussalam Public Health Center, Medan, Indonesia. A quasi-experimental design (non-equivalent group, pre-test–post-test) was conducted from January to October 2024. A total of 140 postpartum working mothers were selected and divided into an intervention group (husbands received structured breastfeeding education with a personalized approach) and a control group (no intervention). Data were collected using structured questionnaires assessing husband’s roles (attention, informational, financial, emotional support) and exclusive breastfeeding practices. Analyses included paired t-tests, independent t-tests, and Pearson correlation tests. Husband involvement significantly increased in the intervention group compared to the control group (p < 0.001) with strong between-group differences (p < 0.001). In the intervention group, scores for all four dimensions of husband’s support were strongly correlated with exclusive breastfeeding success (r > 0.70; p < 0.001), while no significant correlation was found in the control group. Breastfeeding education for fathers through dedicated classes effectively enhances husband involvement in supporting exclusive breastfeeding. Integration of such programs into maternal and child health services, supported by standardized educational modules and digital media tools, is recommended to strengthen husband engagement.